PENGARUH VARIASI DAYA LAMPU UV-C TERHADAP PENURUNAN ANGKA KUMAN ALAT MAKAN DI PT. X (Politeknik Kesehatan Kemenkes Bandung, 2021)
Cleanliness of cutlery is important because unclean eating utensils can cause organisms left behind to breed and contaminate food. PT. X provides food for employees on shift 2. Examination of the number of germs on cutlery after the inspection is carried out, which is 600 colonies/cm2 and exceeds the quality standard for the number of germs in the Indonesian Minister of Health Regulation No. 1096/MENKES/PER/VI/2011 concerning Food Sanitation Hygiene, namely 0 colonies/cm2 surface of cutlery. Cutlery that has been washed is stored in the open, this is a factor that causes contamination of cutlery to occur after the washing process. Efforts to reduce the number of germs in this study is sterilization by utilizing radiation rays from UV-C lamps. The purpose of this study was to determine the effect of variations in the power of UV-C lamps on reducing the number of germs on cutlery. This type of research is experimental with a post test with control research design. The population and samples in this study were all plate cutlery in the EHS room of PT. X. The sampling technique for eating utensils is simple random sampling. The results of the examination of germ numbers after being given treatment in contact time of exposure to UV-C rays with a variation of 8 watts showed the average percentage reduction in germ numbers was 80.38%, while for the 15 watt variation the average percentage reduction in germ numbers was 84.87% and on the 30 watt UV-C lamp power variation the average percentage reduction in germ numbers is 92.42%. The results of the analysis of the one way ANOVA test obtained a value. P (0.000) < (0.05), so that there is a difference in the effect of variations in UV-C lamp power on reducing germ numbers on cutlery. Further research is needed on the higher power of UV-C lamps in reducing the number of germs on cutlery.